KSF of family business - Boroš, Petr (2015)
Family business is a business in which family members have a large stake in ownership and also a deciding vote on business operation. This thesis deals with what makes the family businesses thriving. The research is conducted using the Good to Great framework by Jim Collins. Based mainly on quantitative and qualitative survey of 8 Czech companies of various fields and sizes, it was discovered that there are some links between the companies' success. These findings yield a set of recommendations, which is provided in the last chapter.